2019
DOI: 10.1093/mnras/stz145
|View full text |Cite
|
Sign up to set email alerts
|

Type Ia supernovae have two physical width–luminosity relations and they favour sub-Chandrasekhar and direct collision models – I. Bolometric

Abstract: While the width-luminosity relation (WLR) among type Ia supernovae (slower is brighter) has been extensively studied, its physical basis has not been convincingly identified. In particular, the 'width' has not been quantitatively linked yet to a physical time scale. We demonstrate that there are two robust fundamental time scales that 1. can be calculated based on integral quantities of the ejecta, with little dependence on radiation transfer modeling and 2. can be inferred from observations. The first is the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…For the 16 remaining events, the ratio falls in a narrow range centered around t B /t d ≈ 1.65, consistent with the calculations presented in Fig. 6. and is in excellent agreement with the range measured in Wygoda et al (2019). This agreement suggests that t γ can be estimated without integration on bolometric measurements; instead a simple estimate of the peak time (i.e.…”
Section: Comparison With Observationssupporting
confidence: 81%
“…For the 16 remaining events, the ratio falls in a narrow range centered around t B /t d ≈ 1.65, consistent with the calculations presented in Fig. 6. and is in excellent agreement with the range measured in Wygoda et al (2019). This agreement suggests that t γ can be estimated without integration on bolometric measurements; instead a simple estimate of the peak time (i.e.…”
Section: Comparison With Observationssupporting
confidence: 81%
“…t 0 (Swartz et al 1995;Jeffery 1999;Wygoda et al 2019). This time scale, t 0 , is defined by the time at which the effective optical depth for γ-rays is unity, τ γ,eff = 1:…”
Section: Thermalizationmentioning
confidence: 99%
“…Thus on this scale it seems that M Ni ∼ 0.3 M , similar to other Ic-BL SNe (Lyman et al 2016). Because the data have not yet converged to model tracks, we cannot solve directly for t 0 and M Ni using the technique for Ia SNe in Wygoda et al (2019).…”
Section: Radioactive Decaymentioning
confidence: 99%
“…To estimate the nickel mass of AT2018cow,Perley et al (2019a) compared the bolometric luminosity at t ∼ 20 day to that of SN2002ap (whose nickel mass was derived via late-time nebular spectroscopy;Foley et al 2003) and found M Ni < 0.05 M . On this scale, we would expect M Ni 0.05 M for SN2018gep as well.Finally,Katz et al (2013) andWygoda et al (2019) present an analytical technique for testing whether a light curve is powered by radioactive decay. At late times, the bolometric luminosity is equal to the rate of energy deposition by radioactive decay Q(t), because The bolometric light curve of SN2018gep compared to (left) other Ic-BL SNe from the literature(Cano 2013) and (right) to AT2018cow(Perley et al 2019a).…”
mentioning
confidence: 99%